“Ledwosz, where is the key?”, or people and animals in Iwona Siekierzyńska’s short student film “Missy” - Przybylski, Krystian (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Iwona Siekierzyńska school film Missy takes up the theme of a girl’s unfulfilled love for a priest. Her dog named Ledwosz not only accompanies her in the experience of encountering the man in cassock, while his anointing of a sick neighbor, but also triggers the situation that caused her infatuation. This brief and accidental contact with the priest turns out to be a breakthrough experience for the teenage girl looking for love and attention. It means her entering the adult world in which it is easy to miss a crucial moment, or hurt somebody’s feelings quite unconsciously. The young girl’s experience of the brief encounter will remain in her forever. The relation between the female character and her dog from the short film was the inspiration to consider the similarities between Missy and Three Colors: Red, by Krzysztof Kieślowski, who was the artistic supervisor of Siekierzyńska’s film. In both films it is a dog that initiates the process resulting in metaphysical experience for the main characters.